Relationship between vitamin D levels with nutritional status and children's obesity in Saiful Anwar Hospital, Malang - Anik Puryatni; Harjoedi Adji Tjahjono; Hanna Tetty (Pediatric Sciences Journal, 2023)
Background: Obesity is a condition marked by an excessive buildup of body fat tissue and is characterized by a recognizable clinical picture. An imbalance between energy intake and energy output leads to obesity. Both obesity and vitamin D insufficiency are serious health issues of the present. It was claimed that the mobilization of free fatty acids from adipose tissue might be impacted by active vitamin D (1,25-dihydroxy vitamin D). This study aimed to find a relationship between vitamin D levels with nutritional status and children's obesity in Saiful Anwar Hospital. Methods: This study used a cross-sectional approach with a consecutive sampling method. Seventy-five subjects met the inclusion criteria in the Saiful Anwar Hospital Malang pediatric ward in February-March 2022. The samples were then examined for vitamin D levels. Subjects were grouped based on good nutritional status, overweight, and obesity. The basic characteristics of the research subjects included gender, age, anthropometric status, nutritional status, and vitamin D levels. Results: The results showed that vitamin D levels were lower in overweight and obese children (median 17.6 and 14.08 kg/m2) than in normal nutrition children (median 34 kg/m2). Vitamin D and children's nutritional status had a significant relationship (p=0.001). Conclusion: Vitamin D levels and children's nutritional status were significantly correlated, with vitamin D levels being lower in overweight and obese children than in children with normal nutrition.